Rat lungworm Angiostrongylus cantonensis (Chen, 1935) (Nematoda: Strongylida: Metastrongylida) - John Capinera; Heather S. Walden (EDIS)
Like many pest and disease problems, rat lungworm has been slowly spreading around the world. First described by Chen from rats in China, the medical significance of this parasite was overlooked until 1944 when it was found infecting humans in Taiwan. Even then, because the report was published in Japanese, its importance remained largely unknown. In 1955, Mackerras and Sandars found this nematode among rats in Brisbane, Australia, and described its life cycle, including the importance of its molluscan intermediate hosts. This 4-page fact sheet was written by John Capinera and Heather S. Walden and published by the UF Department of Entomology and Nematology, September 2013.